Implementasi Penggunaan Alat Pelindung Diri pada Sinar-X Sesuai Standar Operasional Prosedur Instalasi Radiologi - Mahdania, Helinda; Novita, Rati Dwi; Darmawan, Zulkifli Tri; Arman, Zulkifli; Musdalifah, Indah; Normawati, Sitti (Lontara Journal of Health Science and Technology, 2025)
Implementation of the use of personal protective equipment against X-rays in accordance with the Standard Operational Procedures for Radiological Installations, which has a very important role in reducing the risk of work accidents due to radiation which impact radiographers and patients during radiological examinations. This research was carried out with the aim of finding out how to implement the use of personal protective equipment for X-rays according to standard operating procedures (SOP) for the radiology installation at Ibnu Sina Hospital YW-UMI. This research used quantitative methods using questionnaires given to 8 radiographers. The research results showed that radiology workers were not yet optimal in using Personal Protective Equipment for X-rays in accordance with the Standard Operating Procedures at Ibnu Sina YW-UMI Hospital.